2022
DOI: 10.1177/13623613211073020
|View full text |Cite
|
Sign up to set email alerts
|

A survey of autistic adults, relatives and clinical teams in the United Kingdom: And Delphi process consensus statements on optimal autism diagnostic assessment for adults

Abstract: Accessing adult autism diagnostic pathways can be difficult. This study explored perspectives of UK autistic adults, relatives and clinicians regarding the characteristics of optimal adult autism assessment and diagnostic services. In stage 1, three key stakeholder groups were surveyed about experiences of adult autism diagnostic services (pre-assessment/assessment): 343 autistic adults, 45 relatives and 35 clinicians completed parallel surveys. Information from stage 1 surveys was used to devise statements fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Fourteen clinicians were psychiatrists (40.0%), 16 clinical psychologists (45.7%) and five (14.2%) were nurses, speech and language therapists or senior autism practitioners. Further details on the characteristics of participants can be found in the related article (Wigham et al, 2022).…”
Section: Stage 1 Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen clinicians were psychiatrists (40.0%), 16 clinical psychologists (45.7%) and five (14.2%) were nurses, speech and language therapists or senior autism practitioners. Further details on the characteristics of participants can be found in the related article (Wigham et al, 2022).…”
Section: Stage 1 Resultsmentioning
confidence: 99%
“…A crucial component to expanding post-autism diagnostic support/services is training others, for example, in primary and secondary mental/physical healthcare, adult social care, IAPT and learning disability services. However, while recommended in national guidance (NICE, 2012; SIGN, 2016; Table S1), research has identified that UK specialist autism services lack resources for cascading expertise via training/consultancy (Beresford et al, 2020; Wigham et al, 2022) again highlighting barriers to implementation of NICE CG and QS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire survey for the quantitative analysis consisted of forty questions that comprehensively covered the primary design aspects that need to be considered, in terms of light and color perceptions, before designing interior spaces intended for autistic children. The questionnaire was carefully designed in a lucid and straightforward format from the literature (67)(68)(69)(70)(71)(72)(73). The questionnaire was fine-tuned further in consultation with the therapists.…”
Section: Data Collectionmentioning
confidence: 99%
“…Care pathways are applied internationally as a way of planning and delivering individualised support to specified groups of people through multidisciplinary team working [30]. Within the last decade, evidence has become available to inform standards and practice in pathways for assessment and diagnosis of autism in children and adults [8,9,31].…”
Section: Neurodevelopmental Pathwaysmentioning
confidence: 99%